Integrasi Pendidikan Karakter dalam Lembaran Kitab Kuning Kedalam Kehidupan Santri Sebagai Ciri Khas Pendidikan Islam Nusantara (Studi Kasus di PP Al-mustaqim Bugel Kedung Jepara) - Sholahudin, Sholahudin (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
This research aims to answer two important questions, how is the contribution of pesantren toward national education, and how is the construction of character education within pesantren. The massif of naughty childhood in the level of SMA and many drug abuses come up, its cause gavorment to implementing 2013 curriculum quickly. This research used qualitative methodology, and interview and also observation as approaches. Character eduction in this context understood as implementing essential values in the student so he able to understand, perceive and integrate the core values of education to his self. With observation of pesantren Al-mustaqim, this research show that pesantren able to integrate the values of character to it daily life. And the contruction of character education within pesantren is build from the kitab kuning and also kiai of pesantren which is become role model of his student or santri.